Modelling organizations' structural adjustment to BIM adoption: a pilot study on estimating organisations - Olatunji, Oluwole (International Council for Research and Innovation in Building and Construction, 2011)
SUMMARY: Building information Modelling (BIM) promises a fairly radical revolution in all segments of theconstruction industry. Vital evidence has been used in many studies to elicit how fragmented processes inconventional construction systems, predominantly manual design systems and entity-based CAD often renderdesign and project performance vulnerable. BIM is presented as having attributes that strengthen theframeworks for servicing efficiency in design and project performance. As BIM adoption continues to improve,various stake-holding practices that are involved in developing projects through integrated systems do requireprocess models to help them simplify issues relating to multi-disciplinary integration – a direct opposite of whatthey are used to in fragmented systems. They also need to develop appropriate skills and strategies, includingnew marketing and administrative stratagems, to service intensive collaboration and other ethos of BIM. Theseare some of the inevitable changes to which organizations must respond in order to generate efficient resultswhen adopting and deploying BIM. To examine organizational response to those process changes as promised inBIM, different organization models are explored with emphasis on their functional structures, namely: (1) matrix(2) networked (3) functional (4) divisional structure models. Data were collected from 8 construction andsoftware development organizations in Australia through focus group discussions. 18 participants in core BIMskills took part in the study. Some interesting discoveries were made and reported on the industry’s reactions toBIM adoption. Conclusively, this study confirms the nature and direction of potential changes that BIM trigger.